The hexadehydro-Diels-Alder reaction: Benzyne generation via cycloisomerization of tethered triynes - Fluegel, Lucas L. (Chem Rev, 2021)
The hexadehydro-Diels-Alder (HDDA) reaction is the thermal cyclization of an alkyne and a 1,3-diyne to generate a benzyne intermediate. This is then rapidly trapped, in situ, by a variety of species to yield highly functionalized benzenoid products. In contrast to nearly all other methods of aryne generation, no other reagents are required to produce a HDDA benzyne. The versatile and customizable nature of the process has attracted much attention due not only to its synthetic potential, but also because of the fundamental mechanistic insights the studies often afford. The authors have attempted to provide here a comprehensive compilation of publications appearing by mid-2020 that describe experimental results of HDDA reactions.